TEACHING SPEAKING THROUGH CHAIN STORYTELLING TO THE TENTH GRADE STUDENTS OF SMA SRIJAYA NEGARA PALEMBANG - Lusi Fitriani; Muslih Hambali (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
The objectives of this study were to find out: (1) whether or not there was a significant improvement in speaking skill of students who were exposed to chain storytelling and (2) whether or not there was a significant difference in speaking skill between students who were exposed to chain storytelling and those who were not. The sample of this study was 60 tenth grade students of SMA Srijaya Negara, which were divided into control and experimental group, and each group had 30 students. To collect the data, each group was assigned pretest and post test. The data analyses used paired sample t test and independent sample t test in SPSS. The result from paired sample t test showed that the mean difference in post test and pretest of experimental group was 16.000 at the significance level of p<0.05 and since t obtained was higher than t table (9.649>2.04523), H01 was rejected and there was a significant improvement in speaking skill of experimental group. The highest contribution was given by story elaboration aspect (content), and then followed by pronunciation, vocabulary, fluency and grammar. The result from independent sample t test showed that the mean difference between post test of experimental group and control group was 2.4000 at the significance level of p>0.05 with t obtained<t table (0.942<2.00171), since t obtained was lower than t table, H02 was accepted and there was no significant difference in speaking skill between students who were taught by using chain storytelling and those who were not. Nevertheless, the mean difference from the experimental group was higher than that of control group (16.600>7.133). Keywords: teaching speaking, chain storytelling